Using Emerging Technologies to Support Wellbeing and Resilience for pilots & Enabling the Assessment of Wellbeing Risk in Airline Safety Management Systems - Cahill, Joan (Springer, 2022)
This paper reports on the findings of two anonymous online surveys undertaken with pilots (n=170) pertaining to pilot self-care behaviors, the use of technology to support wellbeing management, and the acceptability of sharing wellbeing information captured using mobile phone apps with aviation employers, to support the analysis of wellbeing risk in safety management systems (SMSs). New mobile phone-based apps might be implemented to support self-care for pilots as part of a phased approach to the promotion of an integrated health and safety culture, and the management of wellbeing risk in aviation safety management systems (SMS). In the short term, there is insufficient trust on behalf of pilots to support such information sharing practices. Accordingly, it is proposed that pending consent, pilots share deidentified wellbeing information using mobile phone apps (and/or a web interface), in a global repository. This repository or ‘wellbeing monitor’ would be accessible to the industry - providing airlines with general trends data and reports, supporting wellbeing management and risk assessment. This will help mitigate existing employee information sharing barriers, build trust, and foster an integrated health and wellbeing culture, which is the prerequisite for the future assessment of wellbeing risk within a company SMS.
14th International Conference on Social Computing and Social Media (SCSM 2022), held as part of the 24th HCI International Conference 2022
PUBLISHED
http://hdl.handle.net/2262/101057
Online
Keywords: Pilots; Wellbeing; Self-care; Mobile Apps; Safety; Digital Engagement; Inclusive Society; Next Generation Medical Devices; Aerospace Operations/Safety; Aviation Safety; Health and Safety Management; Organisational safety culture; Safety II; Safety Management Systems; Wellbeing Risk; flight safety; health and safety